Primary Malignant B-cell Lymphoma of the Epididymis - Jungyo Suh; Hyeon Jeong; Young A. Kim (Urology Case Reports, 2016)
Primary epididymal lymphomas are very rare condition, only 6 case report was published. In 4 of them, initial presentation was non-tender, continuous growth of testis. It can be misdiagnosed with epididymitis, 5 of them was treated by antibiotics before surgery. One patients treated by surgery another 5 makes neoadjuvant therapy, 2 of radiotherapy 3 of chemotherapy. Only one man died after treatment. This case is about 54-year male patients, diagnosed by diffuse large B-cell lymphoma, who treated by surgery and neoadjuvant chemotherapy combined with radiotherapy.